Third Grade Stars - Ransom Candice F. (Troll Associates, 1994)
Amber Cantrell and her friend Delight Wakefield are the most popular girls in third grade. But when they begin gymnastics, Delight turns out to be a star on the balance beam, while Amber can't even turn a handspring. How can Amber be a third grade star when the only thing she's good at is getting in trouble.
66052